Odd squad [videorecording (DVD)] : the movie - Johnson, J. J. (James Anthony), 1980-; Davis, Millie; Presti, Olivia; Kragten, Isaac ([publisher not identified], 2017)
When the Odd Squad is in danger of being disbanded because a rival agency has a gadget that seemingly fixes any problem, the Odd Squad teams up to save the world from destruction.